Study of typology and morphology of stupa variety at the Padepokan Dhammadipa Arama in Malang, East Java - Ferlina Sugata; Venny (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2021)
Religious people generally have a symbol of respect to worship the greatness of role models in their respective religions. This is motivated by different traditions, history, locations, and developments of religion and worship activities that affect the emergence of various types and forms of worship. One of them is a building named stupa. The stupa building as a means of worship accommodates worship activities in Buddhism. The stupa also functions as an object of respect in implementing worship. Padepokan Dhammadipa Ārāma's premises in Malang are architectural stupas buildings similar to the Patirupaka Stupa Shwedagon in Myanmar. Therefore, this study aims to determine the extent to which this replication process occurs in terms of typological and morphological studies, to analyze typology by classifying stupas based on the types of stupas in the world where each culture has its characteristics, and to analyze morphology based on the level of change and tendency of change. The method of this study is a qualitative study with a rationalistic approach. The study results are tabulations of typology and morphology of stupa architecture as a guide for the types and forms of stupa architecture, contributing to the science of Buddhist religious architecture in the Indonesian Archipelago.